Atrial fibrillation inducibility during cavo-tricuspid isthmus dependent atrial flutter ablation for the prediction of clinical atrial fibrillation. (1st August 2017) - Romero, Jorge; Estrada, Rodolfo; Holmes, Anthony; Goodman-Meza, David; Diaz, Juan Carlos; Briceño, David; Kumar, Saurabh; Baldinger, Samuel H.; Valencia, Carolina R; Roth, Norman; Fisher, John D.; Gross, Jay; et al.
Abstract: Background: Atrial fibrillation (AF) and cavo-tricuspid isthmus (CTI) dependent atrial flutter (AFL) are two separate entities that coexist in a significant percentage of patients. Methods: We sought to investigate whether AF inducibility during CTI AFL ablation predicted the occurrence of AF at follow up after AFL ablation. Univariate and multivariate analyses were performed. Results: A total of 154 patients (male: 72%, age: 61 ± 13) with AFL and without history of AF were included. All patients underwent successful CTI dependent AFL ablation demonstrated by bidirectional block. During ablation, AF was seen or induced in 28 (18%) patients. After a mean follow up of 34 ± 24 months a total of 50 patients (32%) were noted with clinically manifest AF. From the patients who had inducible AF during AFL ablation, 50% developed post-procedural AF. From those in whom AF could not be induced, only 29% were documented with AF after ablation. Univariate and multivariate analyses revealed that only age and AF inducibility during AFL ablation were predictors of AF. Univariate analysis (age p  = 0.038 and inducible AF p  = 0.032 with odds ratio of 1.030 [95% CI (1.002–1.059)] and 2.500 [95% CI (1.084–5.765)], respectively) and multivariate analyses (age p  = 0.011 and inducible AF p  = 0.016 with adjusted odds ratio of 1.043 [95% CI (1.010–1.077)] and 3.293 [95% CI (1.250–8.676)], respectively). Conclusion: AF inducibility in patients undergoing CTI AFL without history of AF is a strong predictor of AF occurrence in the future. Appropriate cardiology follow-up must be encouraged in this high-risk population as stroke prevention strategies can be appropriately introduced in a timely matter especially in patients with elevated CHA2 DS2 -VASc scores (≥ 2).